누룩 사용 발효주로 제조한 증류주의 숙성 용기 및 기간에 따른 특성 - 이대형(Dae-Hyoung Lee); 박인태(In-Tae Park); 이용선(Yong-Seon Lee); 서재순(Jae-Soon Seo); 정재운(Jae-Woon Jung); 김태완(Tae-Wan Kim); 김재호(Jae-Ho Kim); 안병학(Byung-Hak Ahn) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
This study aimed to determine the quality characteristics of fermented wine using Nuruk according to the type of aging container (jar or stainless container) and aging time. Alcohol analysis was initiated at 40.4~39.3%, and alcohol contents in the jar and stainless container decreased as aging time increased. Volatile acid content slightly increased in the reduced pressure (RP) jar and stainless container and showed a different result in the atmospheric pressure (AP) container. Amount of acetic acid did not change either in the jar or stainless container as aging time increased. In the case of 2-thiobarbituric acid (TBA), RP was lower than AP after distillation, and TBA value did not change much either in the jar or stainless container. In the case of fusel alcohol by aging time, n-propanol content did not increase either in the jar or stainless container as aging time increased. Iso-butanol content was reduced in the jar but did not change in the stainless container. In the AP container, more aromatic components were measured on the 180th day of aging time than after distillation. High boiling point aromatic components increased in particular. In the stainless container, more aromatic components were generated on the 180th day of aging, but their amount was relatively lower than in the jar. In the jar aging sensory test, the sensory score at RP 50 cmHg was highest on the 180th day of aging. In the case of AP $80^{°}C$ liquor, sensory score on the 180th day was the most improved. 본 연구에서는 누룩 사용 발효주로 제조한 증류주를 국내에서 일반적으로 사용하고 있는 항아리와 스테인리스 용기에 숙성시키며 숙성시간별 증류주의 특성을 검토하였다. 알코올 분석 결과 알코올은 40.4~39.3%로 시작하였으며 숙성기간이 증가함에 따라 항아리와 스테인리스 용기의 알코올은 조금씩 감소하는 경향을 나타냈다. 휘발 산도는 감압증류 항아리 및 스테인리스 용기 숙성에서 약간 상승하였다. Acetic acid의 함량은 숙성기간이 증가함에 따라 항아리와 스테인리스 용기 모두에서 변화하지 않았다. 2-Thiobarbituric acid(TBA)는 증류 직후 감압증류가 상압증류보다 낮았으며 숙성기간이 증가함에 따라 TBA 값은 항아리와 스테인리스 용기 모두 큰 변화가 없었다. 숙성에 따른 증류주의 fusel alcohol 중 n-propanol은 숙성기간이 증가함에 따라 상승하지 않았으며 iso-butanol은 항아리 숙성의 경우 측정값이 감소하였으나 스테인리스 용기는 변화가 없었다. 향기 성분의 경우 항아리 보관에서 증류 직후보다 180일에서 좀더 다양한 향기 성분이 측정되었으며 특히 고비점의 향기 성분들이 많아졌다. 스테인리스 용기 역시 0일차보다 180일에 좀 더 다양한 향기 성분이 나타났으나 그 양은 상대적으로 항아리보다 적었다. 항아리 숙성 관능 결과 180일에는 감압 50 cmHg의 관능점수가 가장 높았으며 상압 $80^{°}C$ 증류주는 0일에 비해 180일의 관능이 가장 많이 향상되었다.